Overexpression of an NF-YC2 gene confers alkali tolerance to transgenic alfalfa (Medicago sativa L.) - Yu, Jinqiu; Yuan, Yuying; Zhang, Wenkai; Song, Tingting; Hou, Xiangyin; Kong, Lingzelai; Cui, Guowen (Frontiers in Plant Science, 2022)
Alkaline stress severely limits plant growth and yield worldwide. NF-YC transcription factors (TFs) respond to abiotic stress by activating gene expression. However, the biological function of NF-YC TFs in alfalfa (Medicago sativa L.) is not clear. In our study, an NF-YC2 gene was identified and transgenic plants were obtained by constructing overexpression vector and cotyledon node transformation system in alfalfa. The open reading frame of MsNF-YC2 is 879 bp with 32.4 kDa molecular mass. MsNF-YC2 showed tissue expression specificity and was induced by a variety of abiotic stresses including drought, salt, and alkali stress in alfalfa. Under alkali stress treatment, transgenic plants exhibited higher levels of antioxidant enzyme activities and proline (Pro), correlating with a lower levels of hydrogen peroxide (H2O2), superoxide anion (O2–) compared with wild-type (WT) plants. Transcriptomic results showed that overexpression of MsNF-YC2 regulated the expression of phytohormone signal transduction and photosynthesis-related genes under normal and alkaline stress treatments. These results suggest that the MsNF-YC2 gene plays crucial role enhance alkali adaptation abilities in alfalfa.